Mutations in prickle orthologs cause seizures in flies, mice, and humans. - Tao, H.; Manak, J.R.; Sowers, L.; Mei, X.; Kiyonari, H.; Abe, T.; Dahdaleh, N.S.; Yang, T.; Wu, S.; Chen, S.; Fox, M.H.; Gurnett, C.; et al. (American Journal of Human Genetics, 2011)
Epilepsy is heritable, yet few causative gene mutations have been identified, and thus far no human epilepsy gene mutations have been found to produce seizures in invertebrates. Here we show that mutations in prickle genes are associated with seizures in humans, mice, and flies. We identified human epilepsy patients with heterozygous mutations in either PRICKLE1 or PRICKLE2. In overexpression assays in zebrafish, prickle mutations resulted in aberrant prickle function. A seizure phenotype was present in the Prickle1-null mutant mouse, two Prickle1 point mutant (missense and nonsense) mice, and a Prickle2-null mutant mouse. Drosophila with prickle mutations displayed seizures that were responsive to anti-epileptic medication, and homozygous mutant embryos showed neuronal defects. These results suggest that prickle mutations have caused seizures throughout evolution.